Islamic Law Analysis of the Practice of I’anah ‘ala al-ma’shiyah in Shuttle Rental Services - Zainul Anwar (Al-Fiqh: Journal of Contemporary Islamic Law, 2025)
This study aims to analyze the practice of I’anah ‘ala al-ma’shiyah (assisting in sinful acts) in shuttle rental services in Kuta District, Bali, from an Islamic law perspective. This phenomenon arises because some service providers are indirectly involved in activities that are contrary to sharia, such as taking tourists to nightclubs or locations that are synonymous with sin. This study uses a qualitative approach, including fieldwork and in-depth interviews with service providers, religious figures, and service users. The results of the study indicate that most service providers are aware of their potential involvement in the practice of I’anah ‘ala al-ma’shiyah, but still do it for economic reasons and work demands. From an Islamic law perspective, such involvement is included in the category of ta’āwun ‘ala al-ithm, which is prohibited. However, there are different views regarding the level of legal responsibility of service providers. The implications of this study emphasize the importance of Sharia education for service business actors and the need for alternative businesses that align more closely with Islamic principles, especially in tourist areas with high potential for sin.